Rupa Ragam Hias Batik Bernuansa Islam Keraton Cirebon Setelah Masa Pra-Islam - Aquamila Bulan Prizilla (JURNAL RUPA, 2016)
Ornament depictions on the archipelago batik fabrics are much influenced by foreign cultures. Indonesia as an Islamic country also majority diverse country with the world's largest Islamic population, but there are still many Indonesian people do not know how such a batik decoration Nusantara Islamic nuances and how the influence of Islamic culture. The Koran does not mention specifically the image or depiction of law. But batik decoration nuances of Islam Indonesia can be based on hadis, decoration that has a historical background of Islam, and the Islamic philosophical or told him about Islam. The study was confined to the nuances of Islamic ornament palace Cirebon batik after pre-Islamic times. With the goal on the basis of the preservation and dissemination of decorative nuances of Islam in the archipelago, in purpose that Indonesian can can be familiar with batik ornament which is has Islamic nuances, specially batik ornament from Cirebon palace pra-Islam which is has Islamic nuances. The study will use qualitative methods by means of a literature study, expert interviews and field surveys.